Pandemic Perspective: Commonalities Between COVID-19 and Cardio-Oncology - Brown, Sherry-Ann; Zaharova, Svetlana; Mason, Peter; Thompson, Jonathan; Thapa, Bicky; Ishizawar, David; Wilkes, Erin; Ahmed, Gulrayz; Rubenstein, Jason; Sanchez, Joyce; Joyce, David; Kalyanaraman, Balaraman; et al. (Frontiers in Cardiovascular Medicine, 2020)
Overlapping commonalities between coronavirus disease of 2019 (COVID-19) and cardio-oncology regarding cardiovascular toxicities (CVT), pathophysiology, and pharmacology are special topics emerging during the pandemic. In this perspective, we consider an array of CVT common to both COVID-19 and cardio-oncology, including cardiomyopathy, ischemia, conduction abnormalities, myopericarditis, and right ventricular (RV) failure. We also emphasize the higher risk of severe COVID-19 illness in patients with cardiovascular disease (CVD) or its risk factors or cancer. We explore commonalities in the underlying pathophysiology observed in COVID-19 and cardio-oncology, including inflammation, cytokine release, the renin-angiotensin-aldosterone-system, coagulopathy, microthrombosis, and endothelial dysfunction. In addition, we examine common pharmacologic management strategies that have been elucidated for CVT from COVID-19 and various cancer therapies. The use of corticosteroids, as well as antibodies and inhibitors of various molecules mediating inflammation and cytokine release syndrome, are discussed. The impact of angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) is also addressed, since these drugs are used in cardio-oncology and have received considerable attention during the COVID-19 pandemic, since the culprit virus enters human cells via the angiotensin converting enzyme 2 (ACE2) receptor. There are therefore several areas of overlap, similarity, and interaction in the toxicity, pathophysiology, and pharmacology profiles in COVID-19 and cardio-oncology syndromes. Learning more about either will likely provide some level of insight into both. We discuss each of these topics in this viewpoint, as well as what we foresee as evolving future directions to consider in cardio-oncology during the pandemic and beyond. Finally, we highlight commonalities in health disparities in COVID-19 and cardio-oncology and encourage continued development and implementation of innovative solutions to improve equity in health and healing.